Penentuan Percepatan Penyelesaian Proyek Pada Metode Jalur Kritis dengan Program Crash - Wasono Wasono; Fidia Deny Tisna Amijaya; Moch Nurul Huda (EKSPONENSIAL, 2019)
A project requires scheduling so that project completion time can be completed at the targeted time. Critical Path Method (CPM) is one of the scheduling methods that is able to provide solutions to scheduling problems. This method has several project acceleration methods to get the fastest turnaround time with a minimal increase in costs. The acceleration method is the program crashes by not using free float time. Case studies of project scheduling at the bus terminal administration office building in city X have been carried out. Analysis is carried out to obtain a critical path at normal times. At normal times, the implementation time is 385 days with a total cost of Rp. 488,488,000.00. After that the project was accelerated by using a crash program by not using the free float time and the implementation time being 289 days with a direct total project cost of Rp. 520,239,992.00. Based on the time of the acceleration of the crash by not using the free float time, the reduction time was 96 days with the addition of a total direct cost of Rp. 14.252.008.00